Analytical model of wheel-rail contact force due to the passage of a railway vehicle on a curved track - Otero-Yugat, Jesús; Martínez-Miralles, Jordi; De los Santos, María (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
The relationship between the displacements of the wheel contained within the plane of wheel-rail contact and present during the movement of a train on curved tracks is one of the most important problems of the dynamic railway, modeling through a complex and nonlinear physical phenomenon. In order to analyze the dynamics of a coach that moves along a curve, a global model has been developed which includes the characterization of the track and the fixations, stiffness and damping of the bogie and the identification of global conditions in the wheel-rail contact area. The present article describes an analytical formulation that allows the estimation of the dynamic state due to the passage of a railway vehicle, summarizing the results and simulations derived from the application of that model, under the consideration that the contact between wheel and rail is constant, and thus the turn of the wheelset is due to the path tread.